Novel observations of an oceanic whitetip (Carcharhinus longimanus) and tiger shark (Galeocerdo cuvier) scavenging event - Scott, Molly; Miller, Olivia; Stapleton, Devon; Grant, Kayleigh (Frontiers in Fish Science, 2025)
Oceanic whitetip sharks, Carcharhinus longimanus, are known to be common scavengers; however, observations of C. longimanus scavenging events are extremely rare due to their classification as an oceanic pelagic species, typically solitary in nature. On April 9, 2024, over 8.5 h, at least nine C. longimanus were observed scavenging from a heavily degraded carcass off the coast of Kailua-Kona, Hawai‘i, USA. Five tiger sharks (Galeocerdo cuvier) were also observed scavenging on the same carcass. Simultaneous feeding within and between species occurred; however, no agonistic or aggressive interactions were observed. Although a small snapshot, this stochastic event sheds new light on trophic relationships and social interactions among aquatic apex predators that do not normally overlap in space and time.